Drive-Cycle Simulations of Battery-Electric Large Haul Trucks for Open-Pit Mining with Electric Roads - Lars Lindgren; Anders Grauers; Jonas Ranggård; Rikard Mäki (Energies, 2022)
Transport of ore and overburden in open-pit mines is often performed with large haul trucks. Battery-electric operation of haul trucks can significantly reduce the CO2 emissions and the fossil fuel dependence of open-pit mining. This simulation study investigates the feasibility and economy of operating large haul trucks battery-electrically, charging from an electric road system in the form of overhead trolley lines. The used simulation model is verified against measurements on diesel-electric haul trucks in normal operation. The simulation model is then tested with five drive cycles representing typical operations in the Aitik copper mine in northern Sweden. This simulation study shows that battery-electric operation with an electric road is feasible. It is shown that battery-electric operation is much cheaper than diesel-electric operation under reasonable assumptions. It is also much cheaper than diesel-electric operation assisted by an electric road.